Survey Kondisi Fisik Pesilat Rodjo Abang di Kecamata Karangrayung Kabupaten Grobogan (Indonesian Journal for Physical Education and Sport, 2023)
The goal to be achieved in this study is to determine the physical condition of the fighter Rodjo Abang, Karangrayung District, Grobogan Regency. The method used is descriptive quantitative. The sample used was purposive sampling, namely adult fighters (17-35 years) totaling 41 fighters, 13 female fighters and 28 male fighters at Club Rodjo Abang. The instrument used to measure the fighting category fighter is a special measurement test for the fighting category fighter which consists of 9 physical condition test items, namely 300 meter run, bleep test, 1 minute sit up, 1 minute back up, 40 meter sprint, side split, shuttle run, 30 second push ups, standing triple jump. The data analysis technique of this research uses quantitative descriptive analysis with percentages assisted by SPSS. Physical condition test results speed, power, endurance, agility, flexibility, strength. The results obtained were 13 fighters in the moderate condition category, 25 pesilat in the good condition category and 3 pesilat in the very good condition category, this assessment is based on the overall classification of the item scores. Physical condition factors are very influential for athlete achievement because the basis of all sports is the athlete's physical condition by adjusting each sport